Effects of Non-Thermal Plasma Treatment on Seed Germination and Early Growth of Leguminous Plants-A Review - Šerá, Božena; Scholtz, Vladimír; Jirešová, Jana; Khun, Josef; Julák, Jaroslav; Šerý, Michal (Plants (Basel, Switzerland), 2021)
The legumes (Fabaceae family) are the second most important agricultural crop, both in terms of harvested area and total production. They are an important source of vegetable proteins and oils for human consumption. Non-thermal plasma (NTP) treatment is a new and effective method in surface microbial inactivation and seed stimulation useable in the agricultural and food industries. This review summarizes current information about characteristics of legume seeds and adult plants after NTP treatment in relation to the seed germination and seedling initial growth, surface microbial decontamination, seed wettability and metabolic activity in different plant growth stages. The information about 19 plant species in relation to the NTP treatment is summarized. Some important plant species as soybean (Glycine max), bean (Phaseolus vulgaris), mung bean (Vigna radiata), black gram (V. mungo), pea (Pisum sativum), lentil (Lens culinaris), peanut (Arachis hypogaea), alfalfa (Medicago sativa), and chickpea (Cicer aruetinum) are discussed. Likevise, some less common plant species i.g. blue lupine (Lupinus angustifolius), Egyptian clover (Trifolium alexandrinum), fenugreek (Trigonella foenum-graecum), and mimosa (Mimosa pudica, M. caesalpiniafolia) are mentioned too. Possible promising trends in the use of plasma as a seed pre-packaging technique, a reduction in phytotoxic diseases transmitted by seeds and the effect on reducing dormancy of hard seeds are also pointed out.
Keywords: low temperature plasma; seedling; plasma treatment; legumes; Fabaceae; seed